Factors Affecting Talent Manager Performance: Study on the Food Manufacturing Industry in the Cikarang Industrial Area, West Java - Subrata, Karno; Wibowo, Wibowo; Umar, Husein; Riyadi, Hanes; Widyastuti, Sri (Technium Social Sciences Journal, 2021)
This study purposes of analyzing and develop the factors that affect talent managers' performance (Study on the food manufacturing industry in the Cikarang industrial area, West Java). The research design taken is a causal study that explains the relationship between variables and descriptive analysis that explains the data from the indicators and each variable's dimensions. The research object included 14 companies in the food processing industry with a sample of 269 talent managers. The research data is in the form of primary data obtained from filling out questionnaires by respondents. The analytical method used is descriptive statistics, namely percentage, average, and chi-square, using SPSS software and Structural Equation Modeling (SEM) utilize LISREL software. The results of the descriptive study concluded that organizational culture is good. However, organizational culture has not been fully implemented in managing human resources, especially talent managers, because there is still a decentralization process in each different department. Hence, the talent manager's performance is relatively good except for the reservation and reservation dimensions, standards for measuring talent performance. The conclusion of this study states that the proposed research model has not been proven to be successful. The novelty element of this study cannot prove all the hypotheses that have been established as a research model. Therefore it can see from two sides, namely the academic side, by looking at the results of research that reject the hypothesis (anomaly), namely: organizational culture has no effect on job satisfaction. talent manager, organizational culture does not affect HRM, transformational leadership does not affect talent manager performance, and HRM does not affect talent manager performance. The practical side of this research's novelty element is the conservation dimension of the talent manager performance variable, namely the attitude or activity of maintaining work peace, protecting or maintaining work facilities and infrastructure, which is an element of novelty that rejects what should be, likewise with the exciting dimension of transformational leadership, namely the process of stimulating subordinates to think creatively and innovatively.